2017
DOI: 10.1016/j.ijfoodmicro.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural factors affecting Fusarium communities in wheat kernels

Abstract: Fusarium head blight (FHB) is a devastating disease of cereals caused by Fusarium fungi. The disease is of great economic importance especially owing to reduced grain quality due to contamination by a range of mycotoxins produced by Fusarium. Disease control and prediction is difficult because of the many Fusarium species associated with FHB. Different species may respond differently to control methods and can have both competitive and synergistic interactions. Therefore, it is important to understand how agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 64 publications
(88 reference statements)
6
46
0
2
Order By: Relevance
“…The impact of temperature was not evaluated because the average temperatures in the crucial period of ear infection were similar throughout all investigation years and did not exceed 17-19°C. The present investigation showed that F. avenaceum was the dominant species, which agrees with several other findings [25][26][27]. Similarly, a high occurrence of F. poae was detected in our research, which also supports the data in the literature [22,28].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The impact of temperature was not evaluated because the average temperatures in the crucial period of ear infection were similar throughout all investigation years and did not exceed 17-19°C. The present investigation showed that F. avenaceum was the dominant species, which agrees with several other findings [25][26][27]. Similarly, a high occurrence of F. poae was detected in our research, which also supports the data in the literature [22,28].…”
Section: Discussionsupporting
confidence: 93%
“…In Sweden, ploughing has been recognized as an important tool to control Fusarium head blight [26]. On the other hand, Blandino et al [9] determined that the successful control of Fusarium head blight could be achieved only by combining different factors; a single factor, such as the management of plant residues, was not effective.…”
Section: Discussionmentioning
confidence: 99%
“…This was made plain in my mock communities through the formation of an "unclassified Fusarium" phylotype, and the reassignment of reads to and from this phylotype during data processing. It is well known that the ITS locus is not well suited to differentiating among Fusarium species and that alternative markers perform better for this genus (Karlsson, Friberg, Kolseth, Steinberg, & Persson, 2017;Walder et al, 2017). Where taxa of particular interest are known from the start, use of taxon-specific marker genes may be desirable.…”
Section: Inclusionmentioning
confidence: 99%
“…Wheat kernels infected with fungi of the genus Fusarium appear shrivelled; they are lightweight, chalky and covered with mycelia with white or pink discoloration [9]. Fungi of the genus Fusarium cause cereal diseases such as Fusarium head blight (FHB) which decreases yields and has serious economic consequences [10]. FHB disease is caused by several Fusarium species, including mainly Fusarium graminearum, Fusarium culmorum, Fusarium avenaceum and Fusarium poae, as well as Fusarium equiseti, Fusarium langsethiae and Fusarium sporotrichioides.…”
Section: Introductionmentioning
confidence: 99%
“…Mycotoxin-contaminated grain is harmful for humans and animals, and it is not suitable for the production of food and feed [10]. Mycotoxins can cause diseases of the liver, kidneys, nervous system and immune system [12].…”
Section: Introductionmentioning
confidence: 99%